The Problems Of Pre-Reading Instruction In Thematic Learning At Grade 2 SDN 09 Bandar Buat, Kecamatan Lubuk Kilangan, Padang - Rahmelda, Desri; Fitri Windi, Idil; Susanti, Reka (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2022)
This study aims to analyze the problems of early reading in thematic learning in class II at SDN 09 Bandar Create, Lubuk Kilangan District, Padang. This study uses a qualitative approach with a descriptive type. The subjects of this research are class II teachers and students. This research was conducted at SDN 09 Bandar Create, Lubuk Kilangan District, Padang in June 2022. The data collection techniques used were observation, interviews and documentation. The results showed that in applying good reading learning outcomes to students, the teacher could apply thematic learning in students' reading problems, doing a preparation and planning. In the planning, among others, the first to look at the students' reading ability and determine the learning objectives to be implemented. Second, the teacher uses thematic reading teaching materials to guide students in learning to read. The three teachers use the media to guide students in reading activities